2022
DOI: 10.3389/fnut.2022.888317
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tibetan Habitual Food and Metabolic Syndrome Among Tibetan People in China: A Cross-Sectional Study

Abstract: BackgroundThe association between habitual food intake in Tibet and metabolic syndrome (MetS) is largely unclear.ObjectiveTo examine the association between Tibetan habitual food intake and MetS among Tibetan adults.MethodsA population-based cross-sectional study, named the China Multi-Ethnic Cohort (CMEC) study, was conducted between 2018 and 2019. We used data from all Tibetans in the CMEC in the current study. The participants, 1,954 men and 3,060 women aged 18–79 years, were from Lhasa, Tibet Autonomous Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…For example, the Nantong Metabolic Syndrome Study reported that 21.6% participant had MetS, and vigorous physical activity was associated with 15-40% decreased odds of metabolic syndrome (29). Another nationwide study of 4,865 adults from the China Health and Nutrition Surveys reported (32,33). The difference in prevalence rate of MetS among Tibetans and a mixture of Han Chinese also reveals the higher prevalence of MetS in minority group Tibetans than the dominate group Han Chinese, suggesting further policy actions to improve health equity in Chinese minority ethnicity groups residing in remote rural areas (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Nantong Metabolic Syndrome Study reported that 21.6% participant had MetS, and vigorous physical activity was associated with 15-40% decreased odds of metabolic syndrome (29). Another nationwide study of 4,865 adults from the China Health and Nutrition Surveys reported (32,33). The difference in prevalence rate of MetS among Tibetans and a mixture of Han Chinese also reveals the higher prevalence of MetS in minority group Tibetans than the dominate group Han Chinese, suggesting further policy actions to improve health equity in Chinese minority ethnicity groups residing in remote rural areas (34).…”
Section: Discussionmentioning
confidence: 99%
“…The MetS prevalence of 32.9% in this study is similar to the results of a study among a group older Tibetans in Jiarong (Northwest Sichuan Province) using similar diagnosis criteria, which reported the MetS prevalence of 37.6% ( 20 ). Other studies using the China Multi-Ethnic Cohort reported the prevalence of MetS of 17.8% among Tibetans while 11.9% among both Tibetans and Han Chinese using a stricter National Cholesterol Education Program Adult Treatment Panel III (ATP III) criteria ( 32 , 33 ). The difference in prevalence rate of MetS among Tibetans and a mixture of Han Chinese also reveals the higher prevalence of MetS in minority group Tibetans than the dominate group Han Chinese, suggesting further policy actions to improve health equity in Chinese minority ethnicity groups residing in remote rural areas ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Tibetan population is a unique indigenous population (around 6 million) in China, who live at high altitudes and have unique genetic maps as well as dietary habits compared with Han people 20 . Specifically, their dietary pattern involves high levels of salt addition 21,22 . Meanwhile, Tibetans have the habit of drinking butter tea, which is traditionally made from tea leaves, yak butter, water, and salt.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Specifically, their dietary pattern involves high levels of salt addition. 21 , 22 Meanwhile, Tibetans have the habit of drinking butter tea, which is traditionally made from tea leaves, yak butter, water, and salt. A high salt intake has a strong bearing on BP, especially for salt sensitive ones.…”
Section: Introductionmentioning
confidence: 99%
“…The permanent population of Tibetans accounts for 85.74%. With the development of society and economy, ethnic minorities in plateau areas are more likely to obtain high-oil, high-sugar, and highsodium foods [14]. At the same time, the lack of healthy lifestyles and health interventions, the harsh natural environment with high cold and low oxygen, and complex ethnic cultural traditions and customs have created unique, complex, and severe health problems [15,16] and behavioral risk factors [17].According to a Chinese research, people of the Tibet autonomous region had lower overall health than those in other Chinese provinces [18].…”
Section: Introductionmentioning
confidence: 99%